Short Communication: First report on the occurrence of microplastic contamination in mariculture Eucheuma cottonii from Lancang Island, Kepulauan Seribu National Park, Jakarta, Indonesia - MBARA CHAM; YASMAN YASMAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Cham M, Yasman Y. 2024. Short Communication: First report on the occurrence of microplastic contamination in mariculture Eucheuma cottonii from Lancang Island, Kepulauan Seribu National Park, Jakarta, Indonesia. Biodiversitas 25: 3995-3999. Microplastics (MPs) contamination in marine environments significantly threatens marine ecosystems and human health. This study presents the first recorded occurrence of MP contamination in the macroalga Eucheuma cottonii Weber Bosse, 1913, specifically in samples collected from Lancang Island, Kepulauan Seribu National Park, Jakarta, Indonesia. Fibrous blue MPs, measuring approximately 400 µm, were identified in two samples, each weighing 15 g (wet weight). This finding aligns with previous studies reporting fibrous MPs as the global contaminants in macroalgal populations. Despite the similarity, our findings contrast with those from nearby regions, where fragment MPs were observed as the most abundant form. The interaction between MPs and macroalgae is influenced by factors such as surface texture, chemical composition, and the presence of mucilage. Additionally, MPs have been shown to impact macroalgal health, reducing growth rates and photosynthetic efficiency and increasing oxidative stress, highlighting the need for further research. Considering E. cottonii as an edible macroalga and a critical habitat provider in marine ecosystems, regular monitoring of MPs contamination is essential. This research contributes to a broader investigation of MP contamination, growth patterns, and secondary metabolite production in macroalgae under different cultivation techniques, underscoring the importance of sustainable practices in marine resource management.